Pengembangan Storyboard Untuk Meningkatkan Keterampilan Menulis Cerita Fiksi Pada Peserta Didik Kelas VI MI - Zein, Secondta Habib Syarifah; Sukartiningsih, Wahyu; Suparti, Suparti (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2024)
The learning process of writing fiction stories can be developed through storyboard learning media so that students' writing skills can improve. The purpose of this study was to determine the validity and practicality of the developed storyboards and their effectiveness in improving the ability to write fiction stories. The method used is a combined method and this type of research is development (RnD) with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation. The subjects of the study were 21 students of class VI A MI Masjid Al Akbar Surabaya. Data collection was carried out through observation, interviews, pre-test and post-test sheets, student response sheets and filling out validation instrument sheets. The results showed that the storyboards developed proved to be valid, practical, and effective for improving fiction writing skills in grade VI MI students. The data obtained was also reinforced in the analysis of the SPSS application which obtained significant values of .000 < 0.05 which means there is a difference in pre-test and post-test results.